(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Fatty acid analysis of the five types of locally consumed edible oils (n = 22) was carried out using a Gas Chromatograph (G.C) equipped with a Flame Ionization Detector (FID) and stainless steel packed column. The results showed that sunflower oil contained the highest percentage of long chain mono and polyunsaturated fatty acids (91.49 ± 1.91 %) compared to soybean oil (81.14 ± 1.49 %), mustard oil (86.80 ± 3.07 %), palm oil (53.30 ± 0.36 %) and coconut oil (7.12 ± 0.51 %). Two varieties of mustard oil, low erucic (= 5 %, n=3) and high erucic acid ( >14 %, n=2) and two varieties of sunflower oil, high linoleic-low oleic (61-66 % & 22-27 %, n=2) and low linoleic- high oleic (29-38 % and 53-63 %, n =3) were found. Sunflower oil with the highest percentage of mono and polyunsaturated fatty acids especially the high linoleic- low oleic variety appeared to be superior and most suitable edible oil for mass consumption. Key words: Fatty acid, Gas chomatograph, Sunflower oil, Soybean oil, Mustard oil, Palm oil, Coconut oil. Bangladesh J. Sci. Ind. Res. 42(3), 311-316, 2007